Talent Management Implementation for Millennials as an Effort to Achieve Sustainable Organizational Performance - Katharina, Silvia; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to find out the implementation of talent management at Payzett which is dominated by Millennials, assess its effectiveness based on its contribution to the sustainability of organizational performance, and seek the improvement company can do to achieve organizational performance sustainability through talent management toward Millennials. This research is qualitative research conducted at Payzett, a fintech company in Jakarta, Indonesia. There were 14 key informants got involved in this research who are department heads in the company. This research shows that the implementation of talent management at Payzett has not optimally implemented. There are some improvements needed in order to readjust talent management strategy that can meet the needs of millennials in order to increase individual performance and make positive impact on organizational performance sustainability.